MANFAAT WILLIAM FLEXION EXERCISE TERHADAP KONDISI NYERI PUNGGUNG BAWAH MYOGENIK DENGAN MENGGUNAKAN PEMERIKSAAN ODI DAN SRT : CASE STUDY - Yulis Susanti; Baiq Zuyyinah Khairawati (CV. ADIBA AISHA AMIRA, 2026)
Background : Low Back Pain (LBP) is a common musculoskeletal health problem and a major cause of global disability. It is characterized by pain, muscle tension, or stiffness localized below the costal margin and above the inferior gluteal fold, with or without radiating pain to the lower limbs (sciatica). Purpose : This study aims to analyze the effects of William’s Flexion Exercise on myogenic low back pain using ODI and SRT assessments.. Methods : This case study employed a pre–post test design by comparing ODI and SRT scores before and after intervention. William’s Flexion Exercise was administered twice a week for 6 weeks (12 sessions) in the Cawang community, located at Jl. Mesjid Bendungan No.12A RT.05/RW.05. Results : The findings indicate that six weeks of William’s Flexion Exercise improved functional outcomes. ODI scores decreased from 40%, 38%, and 30% to 20%, 20%, and 18% in subjects Ny. I, Ny. D, and Ny. S, respectively. SRT scores also improved, from 8 cm, 7 cm, and 10 cm to 13 cm, 12 cm, and 15 cm. Conclusion : The intervention applied in this study proved to be highly effective in improving functional ability in individuals with myogenic low back pain. The inclusion of a home exercise program also supported optimal recovery and progress.